Best kept secrets ebook - Brown, Sandra (2013)
From a New York Times bestselling, a savvy attorney in small-town Texas will stop at nothing to catch the man who murdered her mother in this steamy thriller. Lawyer Alexandra Gaither revisits the three men who were with her mother the night she died twenty-five years ago. None of their charms can stop Alex's determined search for the truth–she's not leaving without one of them being arrested and convicted. When Alex's investigation uncovers decades-old intrigues, someone decides she must be stopped. Now, with a one-month deadline to either wrap up the case or drop it for good, Alex must work diligently to catch her mother's killer–and find a way to stay alive.